Perancangan Promosi Wisata Negeri Atas Angin Berbasis Videografi Sebagai Upaya Pengenalan Pariwisata kabupaten Bojonegoro - Siswanto, Edwind Adryan; Martono, Siswo; Yurisma, Dhika Yuan (Jurnal Art Nouveau, 2017)
Bojonegoro Regency is one of regencies in East Java province which is geographically quite unique. This diversity raises exotic nature so that it can be used as a tourist attraction.Therefore, as the introduction of tourism in Bojonegoro, East Java as well as to promote the tourism sector in Bojonegoro, the authors put it in the form of design-based tourism promotion hills videografi.Penelitian uses qualitative methods with data collection technique using observation, interviews, literature, existing studies, and studies competitors. The concept used in the design is the